The association between ionized calcium level and 28-day mortality in patients with sepsis: a cohort study - Dan Niu; Huihui Bai; Yuan Zong (Scientific Reports)
Abstract Ionized calcium is crucial for normal physiological function, and blood calcium disorders are associated with poor prognosis in various diseases. However, the relationship between ionized calcium and outcomes in sepsis patients remains understudied. This study aimed to investigate the association between ionized calcium levels and 28-day mortality in sepsis patients. This was a retrospective cohort study of patients with sepsis in the eICU Collaborative Research Database (eICU-CRD) from 208 distinct ICUs across the United States between 2014 and 2015 that explored, and ultimately we included 4,031 patients with sepsis. Ionized calcium level was the exposure variable, and 28-day mortality after ICU admission was the outcome variable. Binary logistic regression was used to explore the independent effects of ionized calcium on 28-day mortality using nonadjusted and multivariable-adjusted models. A generalized additive model and smoothed curve fitting were used to investigate the non-linear relationship between ionized calcium levels and 28-day mortality. A two-piecewise linear model was used to calculate the odds ratio (OR) and 95% confidence interval (CI) on either side of the inflection point. The remaining 4031 patients with sepsis were enrolled in the final analysis. The mean age of the patients was 64.30 ± 15.93 years, and 2167 patients (53.76%) were males. The overall incidence of 28-day death was 13.05% (526/4031). There was a nonlinear relationship between ionized calcium levels and 28-day mortality in patients with sepsis. When the ionized calcium levels were less than 4.25 mg/dL, the risk of 28-day mortality increased by 51% for every unit of decrease in ionized calcium (OR = 0.49, 95% CI 0.29–0.82, P-value = 0.0066). When the ionized calcium level was greater than 4.65 mg/dL, the risk of 28-day mortality increased by 69% for every unit of increase in ionized calcium (OR = 1.69, 95% CI 1.05–2.72, P-value = 0.0307). For patients with sepsis, the association between the ionized calcium levels and the 28-day mortality risk was a U-shaped curve. A higher or lower ionized calcium level was associated with an increased risk of 28-day mortality in patients with Sepsis.